Pathological and molecular diagnostic study of theileriosis in cattle in Sulaimaniyah province, Iraq: Ali Hussain Hassan 1, Nabil A. Salmo 2, Jabbar, S. Ahmed - Hassan, Ali Hussain (The Iraqi Journal of Veterinary Medicine, 2012)
This study was undertaken with the aims of evaluating the efficiency of the PCR assay in investigation of the epidemiological status of tropical theileriosis in comparison with the classical microscopic examination of Giemsa-stained blood smear and detecting the gross and microscopic pathological changes in some organs of the infected animals. Blood and tissue samples were collected from 50 apparently healthy, tick-infested cattle during the period extended from the 1st of July to the 31st of August, 2008 in the modern slaughterhouse in Sulaimaniyah province. Blood smears were prepared from the blood samples and stained with Giemsa dye. The tissue samples were obtained from normal and lesion-presenting tissues of the lymph nodes, lungs and kidneys were investigated by the naked eye for the presence of any pathological changes. Following gross examination, the tissue samples, of the cattle that showed positive results for Theileria annulata parasites by PCR and Giemsa-stained blood smears, have processed for histopathological preparations.When compared with microscopic examination of Giemsa-stained smears, the PCR assay detected a positive results in 8 (16%) of blood samples that revealed negative microscopy indicating that the PCR is more sensitive in diagnosis of tropical theileriosis. The gross pathological examination revealed lymph nodes enlargement, pulmonary congestion and edema and multiple pale areas in the kidneys. Microscopically, the principle pathological lesion was represented by a marked lymphoproliferative reaction within these organs.